Non Binary and Androgynous Gender Representation of TikTok Influencers in the Digital Era - Werdhaningtyas, Tamalia Dara; Utari, Prahastiwi; Anshori, Mahfud (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2025)
In the digital era, social media such as TikTok, Instagram, and Twitter have become public spaces that facilitate more unrestrained self-expression for Indonesian people. TikTok in particular is an essential platform for non-binary gender individuals and androgynous influencers in shaping identities creatively and performatively. This study aims to analyze the role of TikTok in the construction and representation of non-binary and androgynous gender identities, including ethical challenges as well as emerging audience responses. The research employs qualitative methods, analyzing video content, comments, and community interaction. The results show that TikTok facilitates gender expression and supports online community solidarity, although it is still faced with public bias, stereotypes, and ethical dilemmas around representation. TikTok also contributes significantly to building and affirming non-normative gender identities, but ethical attention is needed to ensure that diversity still respects the social value of society.